2002
DOI: 10.1021/jo025788d
|View full text |Cite
|
Sign up to set email alerts
|

30π Aromatic Meso-Substituted Heptaphyrin Isomers:  Syntheses, Characterization, and Spectroscopic Studies

Abstract: The syntheses of new aromatic 30pi heptaphyrins either through a [5 + 2] or a [4 + 3] acid-catalyzed condensation and oxidative coupling reactions of easily available and air-stable precursors are reported. The methodology followed is not only simple and efficient but also allows synthesis of a range of heptaphyrins with different heteroatoms in the core. The oxidative coupling reactions of modified tripyrranes 11 and tetrapyrranes 12 were found to be dependent on the acid concentration used and as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 49 publications
2
39
1
3
Order By: Relevance
“…[124] Continued advances in the area of heteroatom-containing expanded porphyrin chemistry were also reported by Chandrashekar and co-workers. [125] They obtained, among other species, the new heptapyrrolic macrocycles 135 and 136, and their conformational behavior was studied in detail. In a separate study, Hung et al reported that it was possible to obtain novel C-N bridged systems such as 137 and 138 by starting with an aryl-substituted tristhiophene-containing hexaphyrin analogue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[124] Continued advances in the area of heteroatom-containing expanded porphyrin chemistry were also reported by Chandrashekar and co-workers. [125] They obtained, among other species, the new heptapyrrolic macrocycles 135 and 136, and their conformational behavior was studied in detail. In a separate study, Hung et al reported that it was possible to obtain novel C-N bridged systems such as 137 and 138 by starting with an aryl-substituted tristhiophene-containing hexaphyrin analogue.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the associated characterization chemistry is still in its infancy and it may thus be some time before the properties and potential applications of these new expanded porphyrins become fully appreciated. (125,Scheme 38). [117] A crystal- Figure 43.…”
Section: Figure-eight Tetrathiaoctaphyrin and Dihydrotetrathiaoctaphyrinmentioning
confidence: 99%
“…A family of heteroheptaphyrins containing up to five thiophene or selenophene rings and four meso bridges in various patterns were characterized in solution revealing a variety of diatropic quasi-planar conformations containing at least one inverted subunit. [60] Representative examples of these systems include the uniconcave trithiaheptaphyrin 60b-H 2 (T0 B , t FI = 1.28), biconcave tetrathia species 59b-H (T0 A,D , t FI = 1.06), and uniconcave pentathiaheptaphyrin 58b (T0 C , t FI = 1. 19).…”
Section: Heptaphyrinsmentioning
confidence: 99%
“…Die Makrocyclen zeigten diatrope quasiplanare Konformationen mit mindestens einer invertierten Untereinheit. [60] Beispiele sind das unikonkave Trithiaheptaphyrin 60b-H [250] Symmetrie und Linienverbreiterung im Raumtemperatur-1 H-NMR-Spektrum lassen auf einen dynamischen Prozess schließen, aber das Konformationsverhalten von 66 e wurde bislang nicht untersucht.…”
Section: Heptaphyrineunclassified